Testing cognitive models of decision making: selected studies with starlings - Kacelnik, A; Vasconcelos, M; Monteiro, T (Springer, 2022)
The behavioural sciences are home to controversies that have survived for centuries, notably about the relation between observable behaviour and theoretical constructs addressing out-of-sight processes in the agents’ brains. There is no shared definition for cognition, but the very existence of a thriving journal called Animal Cognition proves that such controversies are still live and help to (a) promote research on the complexity of processes leading to action, and (b) nudge scholars to restrict their cognitive models to those that can be falsified experimentally. Here, we illustrate some of these issues in a limited arena, focusing on the construction and expression of subjective value and choice. Using mainly work from our own laboratory, we show that valuation of alternatives is sensitive to options’ properties, to subject’s state, and to background alternatives. These factors exert their influence at the time the subject learns about individual options, rather than at choice time. We also show that valuation can be experimentally dissociated from the cognitive representation of options’ metrics and argue that experimental animals process options independently at the time of choice, without elaborated comparisons along different dimensions. The findings we report are not consistent with the hypothesis that preference is constructed at the time of choice, a prevalent view in human decision-making research. We argue that animal cognition, viewed as a research program at the crossroads of different behavioural sciences rather than as a debate about properties of mental life, is inspiring and solid, and a progressive and progressing paradigm.